Simulation of the ventilation losses in the crankcase of an internal combustion engine. (16th December 2009) - Edelbauer, Wilfried; Diemath, Andreas; Kratochwill, Heinrich; Brenn, Gunter
The reduction of CO2 emissions from internal combustion engines by increasing their efficiency becomes more and more important. Improved efficiency may be achieved by decreasing ventilation losses due to the pumping in the crankcase. Computational Fluid Dynamics (CFD) was rarely used for simulating the crankcase flow so far. This work presents a new model for the prediction of the windage and breathing losses, and applies a model for the blow-by flow. The complete moving crank drive is resolved. The simulation of one engine cycle shows the complex three-dimensional gas flow field, resulting in the crank angle resolved ventilation loss moment.